Jach-Su-Tal, Tadschikistan - Teufer, Mike (e-Forschungsberichte des DAI, 2023)
The field campaigns in the Jach-Su valley (South Tajikistan) in 2012 and 2013 shed new light on the settlement history of the end of the 3rd and 2nd millennium BC, on the beginning of the Bronze Age occupation and especially on the transition to the Iron Age. The excavation in the necropoles of Gelot made it possible to reveal a burial complex contemporary with or earlier than the Bactria-Margiana Archaeological Complex. During a survey of the northern Jach-Su valley in 2010, a Bronze Age settlement was discovered on a loess terrace in Saridjar, 20 km to the north-east of Gelot. Excavations in 2012 and in 2013 prove that we are dealing with a 200 × 200 m large settlement with at least three building phases. Excavations on the site of Karimberdy were reopened in 2012 and 2013. Here, pits and pit houses were found which belong to the Early Iron Age.